Oscillation and nonoscillation for second-order nonlinear neutral functional dynamic equations on time scales - Xun-Huan Deng; Qi-Ru Wang (Electronic Journal of Differential Equations, 2013)
In this article, we investigate the oscillation and nonoscillation of second order nonlinear neutral dynamic equations with retarded and advanced arguments by means of the theory of upper and lower solutions for related dynamic equations along with some additional estimates on positive solutions. We also apply the Kranoselskii's fixed point theorem to obtain nonoscillation results. Some interesting examples are given to illustrate the versatility of our results.